Silk for silver : Dutch-Vietnamese relations, 1637-1700 - Hoàng, Anh Tuấn (TANAP monographs on the history of the Asian-European interaction, 2007)
Based on a wealth of so far unused primary sources from the Dutch East India Company archives, this work explains how Dutch and Chinese maritime traders played a critical role in Tonkin's dramatic emergence as a trading power.